Human Rights and Literature: A Study of The Seven Moons of Maali Almeida - Sharma, Navin; Tripathi, Priyanka (SARE: Southeast Asian Review of English, 2023)
This article examines the use of symbolic representations in The Seven Moons of Maali Almeida (2022) to narrate the history of Human Rights (HR) violations. The article argues that the genre of fiction has emerged as a cultural medium for promoting the discourse of HR, moving beyond legal, judicial, and political forums. Building upon the concept of Human Rights Literature (HRL) developed by Pramod K. Nayar, the article conducts a critical analysis of the novel. It analyses 1) the use of fictional narratives to depict HR violations, 2) the role of language and cultural discourse that contribute to the dehumanization and demonization of people and massacres, and 3) how the discursive description of HR violations due to riots, civil war, and massacres transforms into a popular language of fiction. The article emphasizes the significance of fiction as a valuable addition to ethical literature within the HR movement and as a tool for spreading awareness. Keywords: Human rights, Literature, Fiction, Dehumanization, Genocide